Understanding perceptions of faculty and students about sustainability in Indian business management schools. (26th March 2021) - Kumar, Sushil; Afreen, Shamama
Sustainable development (SD)/sustainability as a concept has gained prominence following global society's realisation that contemporary models of development cannot sustain for a long time. Businesses, in general, are blamed for unsustainable use of natural resources, large-scale environmental degradation, and increasing economic divide in the society. For businesses to be able to transform themselves towards triple bottom line performance, it is imperative that business managers should have in-depth knowledge, abilities, and right value system. The present study tries to assess these aspects among teachers and students of premier business management schools in India by undertaking a structured questionnaire survey. The results indicate that while these two important groups of stakeholders in SD show more or less right value systems, they significantly lack in knowledge of and abilities to handle various SD issues. The findings have implications for business management education policies and administrations of business management schools in the developing world.